Accumulation of Poly-hydroxy-butyric Acid (PHB) by Bacillus Strain Isolated from Paddy Field of Kathmandu University Premises - Upreti, Deepak; Sapkota, Naresh Prasad; Aryal, Bibek; Shakya, Sangita (Nepal Journal of Biotechnology, 2015)
In this study, the effect of applying nutrient limitation on the production of Poly-hydro-oxy-butyric acid (PHB) from soil bacteria was examined. PHB is a biodegradable polymer which provides a reserve of carbon and energy. PHB was extracted by chloroform dispersion method. The amount of synthesized PHB was determined as crotonic acid by spectrophotometry. We found that Nitrogen limiting condition stimulated PHB accumulation. The highest level of PHB accumulation was observed in DNB-6 strain which accumulated 31 % of the dry mass at 20 % glucose concentration. The probabilistic identification of bacteria by PIBwin software version 1.9.2 showed that the strain DNB-6 was close in nature to Bacillus cereus. Nepal Journal of Biotechnology. Dec. 2015 Vol. 3, No. 1: 2-5